Bumerang Kebijakan: Peran Identitas Nasional dan Norma dalam Kebijakan Ekspor Senjata Jerman ke Arab Saudi dalam Kasus Perang Yaman 2015-2019 - Ayu, Albadii Fadhil Mila; Rosyidin, Mohamad (Journal of International Relations, 2020)
On March 2018, Germany halted arms export temporarily to Saudi Arabia concerning Saudi Arabia’s involvement in Yemeni Civil War. Then on October to November 2018, as a response to the assasination of a journalist named Jamal Khashoggi, Germany stopped all arms export to Arab Saudi. Since Saudi Arabia is one of the biggest arms buyer in the world including for Germany, those actions subsequently caused a decrease in exports value in 2018 compared to 2017. Beside that, Germany also received lots of pressure from European Union countries includin United Kingdom and France. However, Germany decided to stand with their stance, even extended the sanction on March 2019. In analyzing the case, constructivism theory, more specifically, the concept of identity and norms will be used. German identities as a democratic and pacifist country, also human rights as an international norms will be used in this research. This research is an explanative type research, also a qualitative research using congruence analysis method with literature research as data collecting method. The results of this study indicate that only Germany’s identity as a pacifist country and human right norms are influential in the German policy making process.